The Role of Entrepreneurship in Competitive Advantage - Mustafa Muwafaq Yahya Alshafi; Neşe YILDIZ (Academia Open, 2026)
General Background: Entrepreneurship has emerged as a fundamental driver of economic development and organizational sustainability in increasingly competitive global markets. Specific Background: Contemporary organizations face mounting pressure to integrate entrepreneurial principles—including innovation, opportunity recognition, and dynamic capabilities—into their strategic frameworks to maintain market relevance and achieve superior performance. Knowledge Gap: Despite the recognized importance of entrepreneurship in modern economies, a significant disconnect persists between theoretical entrepreneurial concepts and their practical application within organizations, particularly regarding how entrepreneurial activities generate sustainable competitive advantage through the integration of innovation, market responsiveness, and sustainability practices. Aims: This study provides a comprehensive analytical examination of entrepreneurship's role in building sustainable competitive advantage by exploring how entrepreneurial initiatives, innovation processes, market opportunity exploitation, and dynamic organizational capabilities collectively contribute to long-term institutional superiority and resilience. Results: The analysis demonstrates that organizations adopting entrepreneurial thinking with integrated innovation and sustainability principles exhibit superior adaptability to changing economic conditions, enhanced market positioning, and stronger competitive performance compared to traditional institutions, with entrepreneurial ecosystems—encompassing investors, educational institutions, and support networks—providing essential infrastructure for fostering entrepreneurial capabilities and strategic decision-making. Novelty: This research advances understanding by establishing entrepreneurship not as a complementary organizational function but as an essential strategic framework that synthesizes innovation, sustainability, and capability-building for achieving enduring competitive advantage. Implications: Organizations seeking resilience and growth in dynamic environments must adopt comprehensive entrepreneurial approaches that balance economic objectives with environmental and social considerations, supported by robust entrepreneurial education systems and ecosystem development.Keywords : Entrepreneurship, Competitive Advantage, Innovation, Sustainability, Market OpportunitiesHighlight : Innovation-driven practices enable organizations to create long-term value and respond effectively to market dynamics. Opportunity investment and dynamic capabilities strengthen organizational adaptability amid economic and environmental change. Integrated ecosystems involving education, investors, and institutions support sustained growth and organizational resilience.